The effect of head posture on facial soft tissue changes captured by white-light facial scanning - Lim Jae-Beom; Oh Seung-Wook; An Hyun-joon; Park Tae-Joon; Lee Tae-Hee; Park Ki-Ho (Sciendo, 2019)
To investigate whether changes in head posture have significant effects on facial soft tissues during white-light scanning.